Role of Rice Husk Biochar in Improving Soil Physical Properties of ex Gold-Mined Soil - Yulnafatmawita Yulnafatmawita; Syafrimen Yasin; Lusi Maira (UNIVERSITY OF LAMPUNG, 2023)
Mining causes destructive soil properties, especially soil texture, water retention, and transmission. Applying biochar is the best way to improve soil physical properties. A glasshouse experiment was conducted to evaluate the role of biochar on soil physical properties based on a Completely Randomized Design (CRD) with four replicates. The research comprised six treatments (0, 4, 8, 12, 16, 20 t biochar ha-1). The results showed that the ex-gold-mined soil had coarse soil texture (sandy loam), high Bulk Density (BD) (1.43 g cm-3), low Total Soil Pores (TSP) (46.45%), low soil organic matter (SOM) content (1.27 %), very fast hydraulic conductivity (198.8 cm h-1). After biochar incubation, SOM increased (to 3.11%), soil BD decreased (to 1.16 g cm-3), TSP increased (to 54.17 %), water retention increased (at pF 1.0, 2.0, 2.54, and 4.2), plant available water (PAW) increased (into 8.33 %), and hydraulic conductivity decreased (into 24.70 cm h-1). However, applying 20 t biochar ha-1 still needs to bring the soil physical properties of the ex-gold-mined soil back into suitable soil for farming land.